Sentiment Analysis of English Tweets Using Data Mining - Kaur, Amritpal; Baghla, Seema (International Journal of Computer Sciences and Engineering, 2025)
Social media has been used for expressing and sharing the thoughts of people with different events. Sentiment analysis is being used for computing and satisfying a view of a person given in a piece of a text, to identify persons thinking about any topic is positive, negative or neutral. In the present work sentiment analysis has been used to analyze people’s sentiments, opinions, and emotions towards entities. In this work, sentiment 140 tools have been used for the collection of tweets on different topics. The collected tweets have been preprocessed. Different techniques have been used to present work. Classification technique has been used for the analysis of tweets how many positive, negative and neutral tweets. Sentiment analysis algorithm has been used to analyze tweets whether tweets are positive, negative or neutral. An autocorrect option has been also used to correct the sentence. Sentiment analysis has been used parameters such as accuracy, predictive and automation